Cholinergic deficits and galaninergic hyperinnervation of the nucleus basalis of Meynert in Alzheimer's disease and Lewy body disorders. (1st October 2019) - Alexandris, A. S.; Walker, L.; Liu, A. K. L.; McAleese, K. E.; Johnson, M.; Pearce, R. K. B.; Gentleman, S. M.; Attems, J.
Abstract : Aims: Galanin is a highly inducible neuroprotective neuropeptide and in Alzheimer's disease (AD), a network of galaninergic fibres has been reported to hypertrophy and hyperinnervate the surviving cholinergic neurons in the basal forebrain. We aimed to determine (i) the extent of galanin hyperinnervation in patients with AD and Lewy body disease and (ii) whether galanin expression relates to the neuropathological burden and cholinergic losses. Methods: Galanin immunohistochemistry was carried out in the anterior nucleus basalis of Meynert of 27 Parkinson's disease (PD) cases without cognitive impairment (mild cognitive impairment [MCI]), 15 with PD with MCI, 42 with Parkinson's disease dementia (PDD), 12 with Dementia with Lewy bodies (DLB), 19 with AD, 12 mixed AD/DLB and 16 controls. Galaninergic innervation of cholinergic neurons was scored semiquantitatively. For a subgroup of cases ( n = 60), cholinergic losses were determined from maximum densities of choline acetyltransferase positive (ChAT+ve) neurons and their projection fibres. Quantitative data for α‐synuclein, amyloid beta and tau pathology were obtained from tissue microarrays covering cortical/subcortical regions. Results: Significant losses of cholinergic neurons and their projection fibres were observed across all diseases. Galaninergic hyperinnervation was infrequent and particularly uncommon in established AD and DLB. We found that hyperinnervation frequencies are significantly higher in the transition between PD without MCI to PDD and that higher burdens of co‐existent AD pathology impair this galaninergic response. Conclusions: Our results suggest that galanin upregulation represents an intrinsic response early in Lewy body diseases but which fails with increasing burdens of AD related pathology.